Indium-zinc-oxide thin films produced by low-cost chemical solution deposition: Tuning the microstructure, optical and electrical properties with the processing conditions - Izabela Stojanoska; Miha Okorn; Brigita Kmet; Hana Uršič; Vera Gradišnik; Duško Čakara; Janez Kovač; Danjela Kuscer (Heliyon, 2023)
Indium-zinc-oxide (IZO) films were prepared by spin coating an ethanol-ethylene-glycol precursor solution with a Zn/(In + Zn) ratio of 0.36 on glass. The effects of temperature on the structure, microstructure, electrical, and optical properties of the IZO thin films were investigated by thermal analysis, Fourier-transform infrared spectroscopy, X-ray diffraction, electron and atomic-force microscopy, X-ray photoelectron spectroscopy and variable-angle spectroscopic ellipsometry. The prepared IZO thin films heated at 500, 600, and 700 °C in air were transparent, without long-range ordering, and with an RMS surface roughness of less than 1 nm. The lowest electrical resistivity at room temperature, 0.0069 Ωcm, was observed for the 115-nm-thick IZO thin film heated at 600 °C in air and subsequently post-annealed in Ar/H2. The thin film exhibited a microstructure characterized by grains typically 20 nm in size and had no organic residues. This film exhibits uniaxial optical anisotropy due to its ultra-thin lamellae with a high electron density. The ordinary refractive index was fitted as a Tauc-Lorentz-Urbach function, which is typical of an indirect absorption edge occurring in amorphous semiconductor materials. The principal absorption peak with an onset at about 2.8 eV and a Tauc gap energy of ∼2.6 eV is similar to those observed for In2O3. The described process of chemical solution deposition and subsequent curing is promising for the low-cost fabrication of IZO thin films for transparent electronics, and can be used to tune the structure and microstructure of IZO thin films, as well as their electrical and optical properties.